PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASIONAL DAN BUDAYA ORGANISASI TERHADAP KUALITAS PELAYANAN PADA RUMAH SAKIT UMUM DAERAH (RSUD) MABA KABUPATEN HALMAHERA TIMUR - Fadilah Yakub; Abdullah W. Jabid; Fadhliah M. Alhadar (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to determine and test the Influence of Job Satisfaction, Organizational Commitment and Organizational Culture on Service Quality. This study uses a quantitative approach. The population used in this study were all employees of Maba Regional Hospital, East Halmahera Regency, totaling 207 people. The sample in the study using the Slovin technique was 67 respondents. The analysis method for testing the hypothesis in this study used the statistical package for social scientists 25 (SPSS) as a statistical test tool. The test results showed that Job Satisfaction had a significant effect on service quality, Organizational Commitment had a significant effect on service quality, Organizational Culture had a significant effect on service quality